2016
DOI: 10.22159/ijpps.2016v8i10.14160
|View full text |Cite
|
Sign up to set email alerts
|

Serum Irisin and Leptin Levels in Obese and Non-Obese Women With Polycystic Ovary Syndrome With Reference to Glucose Homeostasis

Abstract: Objective: This study was aimed to evaluate the effect of serum leptin level on irisin level in relation to glucose homeostasis that to be associated with hormonal changes (Luteinizing hormone (LH), Follicle-stimulating hormone (FSH), Prolactin (PRL), Testosterone (TES)) in obese and nonobese women with polycystic ovary syndrome (PCOS). Methods:Fifty women with polycystic ovaries syndrome (PCOS) and thirty-four apparently healthy control women with regular menstruation (28±2days) were included in this study bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 52 publications
0
16
0
Order By: Relevance
“…In contrast to adiponectin, leptin levels increase in obesity which is proportional to the degree of adiposity [13,31]. In this study, serum leptin and LAR were higher in both obese T2DM and obese nondiabetic patients with respect to healthy control.…”
Section: Discussionmentioning
confidence: 44%
“…In contrast to adiponectin, leptin levels increase in obesity which is proportional to the degree of adiposity [13,31]. In this study, serum leptin and LAR were higher in both obese T2DM and obese nondiabetic patients with respect to healthy control.…”
Section: Discussionmentioning
confidence: 44%
“…MetS is a multifactorial clinical condition where each of its factors plays a crucial role in the development of clinical disorders such as diabetes and CVD [14]. In addition to diabetes and CVD, numerous clinical studies have also found the association of MetS with other disorders such as sleep-disordered breathing, polycystic ovary syndrome, and some cancer types [15][16][17][18][19].…”
Section: Discussionmentioning
confidence: 99%
“…Also, Ali et al [37] reported that serum irisin levels were not significantly differed from their corresponding controls, in both Another study has been found that circulating irisin was significantly lower in PCOS patients [38] .…”
Section: Histopathological Findingsmentioning
confidence: 92%